1993
DOI: 10.1093/oxfordjournals.aje.a116886
|View full text |Cite
|
Sign up to set email alerts
|

Post-traumatic Stress Disorder in Adolescents after a Hurricane

Abstract: A school-based study conducted in 1990, 1 year after Hurricane Hugo, investigated the frequency and correlates of post-traumatic stress disorder (PTSD) in 1,264 adolescents aged 11-17 years residing in selected South Carolina communities. Data were collected via a 174-item self-administered questionnaire that included a PTSD symptom scale. A computer algorithm that applied decision rules of the Diagnostic and Statistical Manual of Mental Disorders, Third Edition, Revised to the symptoms reported was used to as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
42
2
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(48 citation statements)
references
References 0 publications
3
42
2
1
Order By: Relevance
“…However, the rate of PTSD of children and adolescents at-risk was reported from 3% to 100% (Garrison et al, 1995). The estimated lifetime prevalence of PTSD in the general population ranges from 1% to 14% (American Psychiatric Association, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…However, the rate of PTSD of children and adolescents at-risk was reported from 3% to 100% (Garrison et al, 1995). The estimated lifetime prevalence of PTSD in the general population ranges from 1% to 14% (American Psychiatric Association, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…They accounted for only small effects, however, suggesting that other factors were more important determinants. Preexisting emotional and behavioral problems 26,41,[44][45][46] and prior trauma 27,44 may influence the child's response at the time of exposure and later. Preexisting internalizing symptoms such as anxiety and depression, 25,26,41 which themselves may influence the child's peritraumatic response to a traumatic experience, are especially important.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a literature review (Garrison et al 1993;Glesar et al 1981) had suggested that social constructs such as people's beliefs and subjective interpretation of events can play a role in trauma coping and recovery strategies. Hence personal beliefs, such as perceived abilities of self to recover, were also assessed on an ordinal scale.…”
Section: Critical Literature Review and Development Of Conceptual Framentioning
confidence: 99%